Estimates and determinants of HPV non-vaccination in 14-year-old Canadians: Results from the childhood national immunization coverage survey, 2019 - Aranee Sathiyamoorthy; Mireille Guay; Ruoke Chen (Taylor & Francis Group, 2024)
Human papillomavirus (HPV) infections, the most common sexually transmitted infections, are associated with various health outcomes including anogenital warts and cancers. Despite significant investments in HPV vaccination programs, ensuring adequate vaccination coverage for adolescents remains a challenge in Canada. This analysis used data collected through the 2019 Childhood National Immunization Coverage Survey (CNICS) to determine national estimates of HPV non-vaccination and investigate determinants of HPV non-vaccination for adolescents aged 14-years old in Canada, both overall and stratified by gender. The primary outcome of interest was HPV vaccination status, categorized as vaccinated with at least one dose or unvaccinated. Simple and multiple logistic regression models were used to investigate determinants of HPV non-vaccination. In 2019, an estimated 19.8% of the 14-year-olds in Canada were unvaccinated for the HPV vaccine, with males having higher non-vaccination rates than females (27.0% compared to 12.9%). In the unstratified analysis, factors associated with HPV non-vaccination for 14-year-olds were gender and region of residence. These factors differed by gender - for males, region of residence and respondent's age were significant factors, whereas for females, total household income was a significant factor. These results could help public health officials and policymakers develop and implement tailored interventions to enhance the delivery of HPV vaccination programs for male and female adolescents. By targeting populations that are under-vaccinated, vaccine uptake could be better facilitated to help reduce inequalities in access to the HPV vaccine, which could also potentially reduce disparities in HPV-related health outcomes.